A novel is like an axe that penetrates the chest and tears it open. Inter-view with Luca Galassi (Rivista di Studi e Ricerche sulla criminalità organizzata, 2025)
The article features an interview with Luca Galassi, journalist and writer, and is part of a research project dedicated to the symbolic and social impact of the 1993 Mafia attacks against Italy's artistic heritage. In the contribution, the focus shifts from criminal responsibility to the damage inflicted on art and collective memory. In particular, the article reconstructs the birth of the video ‘The Cure’, which documents the restoration of the painting I Giocatori di Carte by Bartolomeo Manfredi, severely damaged in the 1993 Via dei Georgofili massacre. Finally, the article highlights the value of artistic recovery as a resilience to mafia violence and an act of civil commitment.
Keywords: massacres; mafia violence; collective memory; artistic heritage; civic engagement